FILSAFAT DALAM ILMU EKONOMI (SEBUAH JAWABAN MENGAPA ILMU EKONOMI BERFILSAFAT) - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2012)
Humans are the creators and problem solvers. Of our problem was solved, regardless of the type and shape. So we live on the stack problem. Humans are always in conflict with himself and his environment, because of the causal relationship, coupled with the needs facing ketidaktercapaiannya. With the help of these economics, Humans develop their potential to address the needs of this survival. He thought of new things, because he lives not just for survival, but more than that. Humans develop the culture, people give meaning to life, humans "humanize themselves in life" and many statements of this kind, all that essentially concluded that human life has a purpose in life higher than just survival. This is what causes people to develop the knowledge and knowledge is also likely to push humans into creatures that are typical of this earth.